Kedudukan dan Tanggung Jawab Notaris Penerima Protokol Notaris yang Meninggal Dunia - Eko Permana Putra; Yuliandri Yuliandri; Azmi Fendri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
answer the needs and interests of the community of legal certainty, as stated in the agreements, agreements and agreements made by the parties in the form of authentic deeds. The making of an authentic deed as a perfect proof and no further evidence is needed to strengthen the arguments in a legal case. Authentic deed consists of minuta deed and a copy of the deed. Minutes of deed are kept by a Notary who is part of the Notary protocol which must be kept and maintained by the notary because it is a state archive. Article 1 number 8 of the UUJN states that